2008
DOI: 10.1007/s11606-008-0610-4
|View full text |Cite
|
Sign up to set email alerts
|

A Computerized Aid to Support Smoking Cessation Treatment for Hospital Patients

Abstract: BACKGROUND: Hospital-based interventions promote smoking cessation after discharge. Strategies to deliver these interventions are needed, especially now that providing smoking cessation advice or treatment, or both, to inpatient smokers is a publicly reported quality-of-care measure for US hospitals. OBJECTIVE:To assess the effect of adding a tobacco order set to an existing computerized order-entry system used to admit Medicine patients to 1 hospital. DESIGN:Pre-post study. MEASUREMENTS AND MAIN RESULTS:Propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 6 publications
2
32
0
3
Order By: Relevance
“…More comprehensive policies that include referrals, written materials, and chart reminders may result in even greater rates of parent treatment for tobacco dependence. Not only have multiple randomized trials confirmed that computerized reminders increase outpatient preventive care (Koplan et al, 2008), but one recent study specifically showed that adding a tobacco order set to a hospital's existing computerized order entry system increased referral rates for smoking cessation and nicotine replacement therapy (Koplan, Regan, Goldszer, Schneider, & Rigotti, 2008). Increased access to written materials for parent smokers may also help increase routine cessation counseling by nurses.…”
Section: Discussionmentioning
confidence: 99%
“…More comprehensive policies that include referrals, written materials, and chart reminders may result in even greater rates of parent treatment for tobacco dependence. Not only have multiple randomized trials confirmed that computerized reminders increase outpatient preventive care (Koplan et al, 2008), but one recent study specifically showed that adding a tobacco order set to a hospital's existing computerized order entry system increased referral rates for smoking cessation and nicotine replacement therapy (Koplan, Regan, Goldszer, Schneider, & Rigotti, 2008). Increased access to written materials for parent smokers may also help increase routine cessation counseling by nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians favored the provision of oral versus transdermal patch forms of NRT, and patients hospitalized on dual-diagnosis units were prescribed more NRT and higher doses compared with patients hospitalized on other units (10). Evidence from nonpsychiatric hospital settings indicates that staff training (11) and inclusion of NRT on computerized template orders (12) are associated with greater offering of NRT by providers, whereas consistent and persistent offering of NRT (13) and behavioral and motivational counseling (11,14) are associated with greater utilization of NRT among patients. [References citing additional evidence are listed online in a data supplement to this report.…”
mentioning
confidence: 99%
“…In spillover, clinicians may adopt language or processes from the decision aid into their routine practice, thereby diluting differences between the intervention and usual care groups. 23,24 The majority of trials in the Cochrane review of decision aids were patient-level randomized trials. 3 Clustered randomized trials are particularly important for decision aids that are designed to be used within a clinical encounter.…”
Section: Step 4: Testing the Tool In A Real-world Settingmentioning
confidence: 99%